The synthesis of lipids and proteins in vitro in tissues of Cyprinus carpio infected with Bothriocephalus acheilognathi - Yuskiv, L. L.; Yuskiv, I. D. (Regulatory Mechanisms in Biosystems, 2021)
The problem of the mechanisms of regulation of biochemical processes in carp Cyprinus carpio (Linnaeus, 1758) tissues and organs caused by infection with Bothriocephalus (Schyzocotyle) acheilognathi (Yamaguti, 1934) at different intensities of invasion remains practically unstudied. The purpose of this study was to dedetrmine the intensity of lipid and protein synthesis in vitro when [6-14C]glucose and [2-14C]lysine are used as their precursor in the tissues of the intestine, hepatopancreas and skeletal muscles of carp. The study was conducted on this-year carp with body weight 14.5–20.5 g, at different invasion rates of the helminth B. acheilognathi, which belongs to the family Bothriocephalidae of the Pseudophyllidae order of the Cestoda class of the Plathelminthes phylum. The examined carp were divided into three groups: 1st group of fish was free from intestinal helminths of B. acheilognathi (control); 2nd group of fish was weakly infected with helminths (intensity of invasion was 1–3 helminths per fish); the 3rd group of fish was highly infected (the invasion intensity was 4 worms and more per fish). Our results showed that in fish infected with the helminth B. acheilognathi in comparison to uninfected, the intensity of lipid synthesis in the intestinal wall, hepatopancreas, skeletal muscle was much lower when [6-14C]glucose was used as a predecessor than when [2-14C]lysine was used as a predecessor. In the examined tissues, significant decrease was observed in the synthesis of reserve lipids (mono-, di- and triacylglycerols) in comparison to the structural (phospholipids and cholesterol), which depends on the intensity of the B. acheilognathi invasion. In the metabolic processes in the wall of the intestine, hepatopancreas, skeletal muscle of this-year carp infectd with B. acheilognathi helminths, under in vitro conditions, [6-14C]glucose was used more than [2-14C]lysine. The intensity of protein synthesis in the intestinal wall, hepatopancreas, skeletal muscles of this-year carp infected with the helminth B. acheilognathi under in vitro conditions increased when [6-14C]glucose was added to the incubation medium, on average 7.1–28.3% and decreased when [2-14C]lysine was added, on average 7.8–25.7%.